Limbic system development underlies the emergence of classical fear conditioning during the third and fourth weeks of life in the rat - Deal, Alex L; Erickson, Kristen J; Shiers, Stephanie I; Burman, Michael A (Behavioral neuroscience, 2016)
Classical fear conditioning creates an association between an aversive stimulus and a neutral stimulus. Although the requisite neural circuitry is well understood in mature organisms, the development of these circuits is less well studied. The current experiments examine the ontogeny of fear conditioning and relate it to neuronal activation assessed through immediate early gene (IEG) expression in the amygdala, hippocampus, perirhinal cortex, and hypothalamus of periweanling rats. Rat pups were fear conditioned, or not, during the third or fourth weeks of life. Neuronal activation was assessed by quantifying expression of FBJ osteosarcoma oncogene (FOS) using immunohistochemistry (IHC) in Experiment 1. Fos and early growth response gene-1 (EGR1) expression was assessed using qRT-PCR in Experiment 2. Behavioral data confirm that both auditory and contextual fear continue to emerge between PD 17 and 24. The IEG expression data are highly consistent with these behavioral results. IHC results demonstrate significantly more FOS protein expression in the basal amygdala of fear-conditioned PD 23 subjects compared to control subjects, but no significant difference at PD 17. qRT-PCR results suggest specific activation of the amygdala only in older subjects during auditory fear expression. A similar effect of age and conditioning status was also observed in the perirhinal cortex during both contextual and auditory fear expression. Overall, the development of fear conditioning occurring between the third and fourth weeks of life appears to be at least partly attributable to changes in activation of the amygdala and perirhinal cortex during fear conditioning or expression. (PsycINFO Database Record